The Evolution Of Japanese Haiku: From Paper To Digital (International Journal of Education and Literature, 2024)
Haiku is a type of traditional Japanese poetry that originated in the Muromachi era (13th-15th centuries) and evolved further throughout the Edo era (17th century). Haiku, along with Ninja, Manga, Samurai, and Karaoke, has become a prominent Japanese vocabulary word around the world. Haiku is a form of poetry that can be found in both Japanese and international literature. Haiku has grown in popularity as a result of technological advancements in the twenty-first century, particularly through the internet and social media. This study attempts to summarize the evolution of haiku from paper to digital media as it exists today. Digital platforms have changed the classic haiku structure by allowing for syllable count experimentation, multimedia incorporation, and worldwide cultural interaction. These innovations have enhanced the haiku tradition while preserving its core and depth.